Medical JPEG image steganography based on preserving inter-block dependencies. (April 2018) - Liao, Xin; Yin, Jiaojiao; Guo, Sujing; Li, Xiong; Sangaiah, Arun Kumar
Highlights: We investigate an adaptive data hiding strategy that preserves the differences among DCT coefficients at the same position in adjacent DCT blocks. A novel medical JPEG image steganographic scheme based on the inter-block dependencies is proposed, so as to improve the security of the patients personal information. Experimental results show that the proposed scheme can cluster the inter-block embedding changes and perform better than the state-of-the-art works. Graphical abstract: Abstract: With the development of computer and biomedical technologies, medical JPEG images contain the patients' personal information and the security of the private information attracts great attention. Steganography is utilized to conceal the private information, so as to provide privacy protection of medical images. Most of existing JPEG steganographic schemes embed messages by modifying discrete cosine transform (DCT) coefficients, but the dependencies among DCT coefficients would be disrupted. In this paper, we propose a new medical JPEG image steganographic scheme based on the dependencies of inter-block coefficients. The basic strategy is to preserve the differences among DCT coefficients at the same position in adjacent DCT blocks as much as possible. The cost values are allocated dynamically according to the modifications of inter-block neighbors in the embedding process. Experimental results show that the proposed scheme can cluster the inter-block embedding changes and perform better than the state-of-the-art steganographic method.